Vesicular stomatitis virus Indiana glycoprotein as a T-cell-dependent and -independent antigen. - Freer, G (1994)
The neutralizing immunoglobulin M (IgM) response to vesicular stomatitis virus (VSV) has been shown to be largely T-cell independent in several T-cell-deficient models of mice. By using different antigen froms of VSV, VSV antigen doses could be graded in vivo (infectious > > UV inactivated > formalin inactivated). The present study reveals a T-cell-dependent component of the neutralizing IgM response in nude mice given intravenous injections of low doses of noninfectious UV-inactivated VSV serotype Indiana (VSV-IND) only if the mice are transfused with VSV-IND-specific helper T cells. Instead, nude mice immunized with infectious VSV, which leads to greater antigen doses in vivo, were able to mount an IgM response in the absence of T cells. These results indicate that the IgM response to low doses of VSV-IND glycoprotein (G) is T-cell dependent. Nude mice immunized with infectious VSV also made a variable but low VSV-IND-neutralizing IgG response. A VSV-IND matrix (M)-specific helper T-cell line rendered this response more consistent, much higher, and longer lasting. Thus (i) VSV-G induces a mostly T-cell-independent but partially T-cell-dependent IgM (the latter can be visualized best at low doses of antigen) and (ii) the antibody response to VSV in nude mice proceeds through steps, i.e., IgM and IgG, that are dose dependent. The results suggest that the predominant role of helper T cells may be to expand and maintain the individual steps of differentiating B cells.